Peningkatan Potensi Ekonomi Kreatif Masyarakat melalui Pembuatan dan Pelatihan Budidaya Jamur Tiram dengan Metode Smart Farming - Mukhlidi Muskhir; Doni Tri Putra Yanto; Miftahul Khair (Universitas Negeri Padang, 2022)
Jorong Mudik Malih, Nagari Tanjung Gadang, Tanjung Gadang District, Sijunjung Regency, Sumatera Barat Province is an area with a relatively low level of community economy. While geographically this area has good natural potential for agriculture and animal husbandry. In addition, public knowledge related to the latest agricultural technology such as smart farming methods and the types of agricultural commodities that are needed by the community is still low. Smart farming that apply Information & Communication Technology (ICT) and Internet of Things (IoT) in agricultural management are able to increase productivity and efficiency. To overcome these problems, several solutions are offered, namely: (1) making houses/places for oyster mushroom cultivation with the smart farming method for the local community, (2) providing ready-to-plant mushroom seeds, and (3) training on the management of oyster mushroom cultivation using smart farming method. The smart farming method is the application of watering control equipment and air humidity settings for mushroom cultivation that can be accessed using Android-based devices or gadgets. This activity is divided into 4 stages of implementation, namely the planning, preparation, implementation, and evaluation stages. The results of this activity indicate that the natural conditions in Jorong Mudik Malih are very suitable for oyster mushroom cultivation in conditions of temperature and air that tend to be humid, besides that Smart-farming equipment also functions well because there are clean water and adequate electricity. The community is also enthusiastic about studying and cultivating oyster mushrooms as a new crop commodity in the area. Thus, the results of this service activity are expected to be able to create a source of creative economy for the local community.